PERTANGGUNGJAWABAN PIDANA OKNUM LEMBAGA SWADAYA MASYARAKAT (LSM) SEBAGAI PELAKU TINDAK PIDANA PEMERASAN DALAM HUKUM PIDANA INDONESIA (ANALISIS PUTUSAN PENGADILAN NEGERI JAKARTA UTARA NOMOR 276/PID.B/2020/PN JKT.UTR) - Irsal; Lumban Gaol, Selamat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
Nowadays, several non-governmental organizations or NGOs have deviated and are no longer guided by the rules as they should be. These NGOs carry out their goals and functions, a handful of NGOs carry out illegal services billing and extortion carried out in the area of the NGO itself. Therefore, it is very interesting and important to study further how the criminal act of extortion by non-governmental organizations (NGOs) is regulated in Indonesian criminal law? and What were the considerations of the Panel of Judges in the North Jakarta District Court Decision Number 276/Pid.B/2020/PN Jkt.Utr in convicting the Defendant of a Non-Governmental Organization (NGO) as the perpetrator of the crime of extortion. To answer these problems, normative juridical legal research methods are used with statutory and conceptual regulatory approaches. Data obtained from primary, secondary and tertiary legal material sources were collected and then analyzed using qualitative data analysis techniques. From the research results, it was found that the criminal act of extortion with violence is regulated in Article 368 of the old Criminal Code which is still in effect at this time and the new Criminal Code, namely Article 482 of Law 1/2023 which comes into effect from the date of promulgation, namely 2026. Analysis of Decision Number 276/Pid .B/2020/PN Jkt.Utr for the criminal act of extortion committed by a Non-Governmental Organization (NGO) against Slamet Riyanto, the defendant was sentenced to 6 (six) months in prison. The things that mitigate the defendant include that the defendant has never been punished, admits and regrets his actions.